The Importance of Camel Milk and Its Health Benefits - Hasen, Iman Jaber (Technium BioChemMed, 2024)
Camel milk’s distinctive nutritional qualities and possible health advantages are making it famous around the globe. All around the semi-arid and dry world, people have been considering it as a potential medicinal and nutritional food source. Cow and camel milk are chemically similar; both contain a lot of fat, mostly medium-chain fatty acids, very little lactose, and plenty of iron and vitamin C. It is widely believed that camel milk and its derivatives have antidiabetic, anti-cancer, and antihypertensive effects, among numerous other beneficial health effects. Some of the potential scientific explanations for camel milk’s health benefits have been uncovered by various in vitro and in vivo investigations. These include the presence of bioactive proteins (such as lactoferrin, immunoglobulins, and lactoperoxidases) and the production of bioactive peptides during digestion. Scientists and health nuts alike have taken an interest in camel milk for its unusual nutritional qualities and possible medicinal uses. Scientific investigations into camel milk’s many medicinal, nutritional, and economic uses have yielded promising results. The purpose of this research is to analyse camel milk and investigate its significance while also discussing its many components, benefits, and advantages in terms of health.